Comparative Maternal and Neonatal Effects of the New and the Old Formulations of 2-Chloroprocaine. Issue 3 (July 1988) - Abboud, T. K.; Mosaad, P.; Makar, A.; Gangolly, J.; Dror, A.; Zhu, J.; Mantilla, M.; Zaki, N.; Davis, H.; Moore, J.; Swart, F.; Reyes, A.
Abstract : The effects of epidural bisulfite-free chloroprocaine with and without 1:300, 000 epinephrine during labor and delivery on uterine activity, progress of labor, fetal heart rate, maternal blood pressure, newborn Apgar scores, neonatal acid base status, and the Neurologic and Adaptive Capacity Scoring System (NACS) were studied in 100 parturients. Patients in group I (n=49) received 2% chloroprocaine with 1:300, 000 epinephrine and patients in group II (n=51) received 2% chloroprocaine alone. All patients obtained satisfactory analgesia with chloroprocaine, with no major adverse experience. Duration of analgesia was significantly longer in group I than in group II patients (70.8±3.1 minutes versus 50.4±1.8 minutes, P <0.001 (mean±SE). The addition of epinephrine to chloroprocaine did not have any significant effects on duration of the first or second stages of labor, mode of delivery, or fetal heart rate parameters. Maternal heart rate and the incidence of hypotensive episodes did not differ significantly between the two groups of patients. Apgar scores, neonatal acid-base status, and the NACS were equally good in the two groups of patients. These results were similar to those previously reported using 2-chloroprocaine with 0.2% bisulfite. It is concluded that bisulfite-free chloroprocaine provides satisfactory anesthesia for labor and delivery and does not differ from the old formulation that contains bisulfite. It is also concluded that the addition of epinephrine during epidural anesthesia in the normal parturient has no adverse effects on mother, fetus, neonate, or the progress of labor and it significantly prolongs the duration of anesthesia.